Comparison between open Haemorrhoidectomy versus closed Haemorrhoidectomy - Naeem Ghaffar, Mudassar Ali, Kamran Abbas, Khumair Asif, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The study is about the comparison of open haemorrhoidectomy and closed haemorrhoidectomy. This study is aimed to compare both surgical techniques and to find out the outcomes. Materials and Methods: This study was conducted at sugery department sir Ganga ram hospital Lahore from January 2021 to December 2022. A total of 70 participants were part of the study. The patients of the age group between 20 to 65 years were admitted to the surgery department for planned hemorrhoids surgery. The patients treated with open haemorrhoidectomy were allocated to group 1 while group 2 consists of patients selected for closed haemorrhoidectomy. Before the surgery, consent was signed by the individual patients or their relatives. Exclusion Criteria: The patients suffering from issues like ulcerative colitis, immune deficiency diseases, rectal cancer, Crohns disease, and thrombosed hemorrhoids were omitted from the study. Patients with a previous history of hemorrhoids operation and pregnant women with piles were also excluded from this study. Results: A total of 70 patients were the part of study. 35 of patients for open haemorrhoidectomy considered as group 1 and 35 were the part of close haemorrhoidectomy, considered as group 2. Patients of age 20 to 65 years were included in the study. In group 1, 20 (57.14%) males and 15 (42.85%), females their average age mean was 39. 9 ± 10.11 for both males and females. 27 (77.14%) patients were reported preoperative bleeding, 9(25.71 %) pain and 23 (65.71%) patients had the issue of pruritus. In group 2 the mean age 40 ± 12.2 was reported,22 (62.85%) males and 13 (37.14%) females. Preoperative 25 (71.42%) bleeding cases, 6 (17.14%) with severe pain and 20 (57.14%) had a history of Pruritus. The most common symptom was bleeding. The comparison of open haemorrhoidectomy and closed haemorrhoidectomy is elucidated in Table 2. The operative time for open haemorrhoidectomy was shorter than closed haemorrhoidectomy with a P-value of 0.03. The stay duration at the hospital for the first group was 3 days while 2 days for the second group with non-significant results. The wound healing time was measured less for 2nd group than 1st group. A significant difference was found in wound healing such as for first group,5weeks and for 2nd group,3 weeks. The post-operative pain was observed lesser in group 2 (closed haemorrhoidectomy) than the group 1 (open haemorrhoidectomy). Conclusion: We concluded that a closed haemorrhoidectomy produces less post-operative pain than an open haemorrhoidectomy. Secondly, wound recovery was more quickly in the case of closed haemorrhoidectomy.